Evaluasi Risiko Kebangkrutan PT. Pratama Abadi Nusa Industri Tbk - Irawan, Via Mustika; Ningsih, Indah Sukma (BISMA : Business and Management Journal, 2024)
This research aims to reduce the risk of bankruptcy for PT. Pratama Abadi Nusa Industri Tbk, which is listed on the Indonesia Stock Exchange. Using a quantitative descriptive method with a case study approach, this research analyzes the company's financial reports from 2020 to 2022. The results of the analysis show a significant decline in activity turnover, extremes in the operating expense ratio, as well as volatility and losses in net profit. A decrease in current assets and an increase in liabilities indicate a serious liquidity problem. Overall, these findings indicate serious challenges in operational efficiency and cost management, which can hinder a company's ability to meet short-term obligations and maintain profitability. Strategis steps are needed from company management to improve financial conditions and restore investor confidence.